"Registries are not only a tool for data collection, they are for action": Cancer registration and gaps in data for health equity in six population‐based registries in India. Issue 9 (29th December 2020) - Bhatia, Amiya; Victora, Cesar Gomes; Beckfield, Jason; Budukh, Atul; Krieger, Nancy
Abstract: In India, population‐based cancer registries (PBCRs) cover less than 15% of the urban and 1% of the rural population. Our study examines practices of registration in PBCRs in India to understand efforts to include rural populations in registries and efforts to measure social inequalities in cancer incidence. We selected a purposive sample of six PBCRs in Maharashtra, Kerala, Punjab and Mizoram and conducted semistructured interviews with staff to understand approaches and challenges to cancer registration, and the sociodemographic information collected by PBCRs. We also conducted a review of peer‐reviewed literature utilizing data from PBCRs in India. Findings show that in a context of poor access to cancer diagnosis and treatment and weak death registration, PBCRs have developed additional approaches to cancer registration, including conducting village and home visits to interview cancer patients in rural areas. Challenges included PBCR funding and staff retention, abstraction of data in medical records, address verification and responding to cancer stigma and patient migration. Most PBCRs published estimates of cancer outcomes disaggregated by age, sex and geography. Data on education, marital status, mother tongue and religion were collected, but rarely reported. Two PBCRs collected information on income and occupation and none collected information on caste. Most peer‐reviewed studies using PBCR data did not publish estimates of social inequalities in cancer outcomes. Results indicate that collecting and reporting sociodemographic data collected by PBCRs is feasible. Improved PBCR coverage and data will enable India's cancer prevention and control programs to be guided by data on cancer inequities. Abstract : What's new? In India, cancer registries cover less than 15% of the urban and 1% of the rural population. Given this, can such registries reveal how poverty and social inequalities contribute to unequal cancer incidence? In this study, the authors found that, in many cases, the answer is yes. Equity analysis of cancer‐incidence data in India is feasible, as many registries have collected extensive sociodemographic information. These results indicate that improved coverage and information collection will enable India's cancer prevention and control programs to be guided by data on cancer inequities.